PSECO-IM: An Approach for Incident Management to Support Governance in Proprietary Software Ecosystems - Costa, Luiz Alexandre Martins; Fontão, Awdren Lima; Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Organizations that produce software cooperatively and competitively to satisfy customer needs give more attention in relationships among several actors (e.g., providers, developers, and IT managers) to build the value creation network called Software Ecosystem (SECO). As a type of SECO, proprietary SECO concerns data concentrated on a platform with contributions protected by intellectual property. The technological platform that supports the business initiatives is developed using different technologies with dozens of integration points, promoting a network of dependencies and architectural complexities. Some studies show that systems downtime (incidents) causes major image and financial upheavals for organizations. To mitigate the risks of incidents, the IT management team should implement strategies based on governance mechanisms to sustain the platform. Our work aims to develop and evaluate a process-based approach (PSECO-IM) for incident management to support the IT management team in the governance of a technology platform architecture in a proprietary SECO. We also addressed some of the identified challenges of quality in proprietary SECO, such as standardized software processes, knowledge management, and governance strategies. As a final result, we got positive feedback on the relevance of the tool in improving governance strategies related to incident management by the organization’s practitioners. We argue that this work is appropriate for the Software Quality area since it covers studies on three pillars: people, process, and technology, such as tacit knowledge, low-quality software, governance, incident management, and proprietary SECO.